2015
DOI: 10.1089/aid.2014.0251
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Detection of Antiretroviral Drug Resistance in HIV-1-Infected Orphaned Children Followed at a Donor-Funded Rural Pediatric Clinic in Dodoma, Tanzania

Abstract: A total of 81 HIV-1 protease (PR) and reverse transcriptase (RT) sequences were obtained from 46 drug-naive and 35 pretreated individual HIV-1-infected orphaned children followed at a donor-funded rural pediatric clinic in Dodoma, Tanzania. PR and RT sequencing was performed by home-brew technology on 70 plasma samples and 11 dried blood spot specimens. Nucleoside RT inhibitor (NRTI) resistance mutations were detected in 2.2% of drug-naive and 82.9% of pretreated children. Nonnucleoside RT inhibitor (NNRTI) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…19 Two studies from Dodoma, Tanzania, report resistance data from different populations including HIV-infected, ART naive pregnant women with 7.5% harboring NNRTI mutations 20 and ART naive children Maternal regimen sdNVP1tail (n = 10) 3 (30%) 7 (70%) 6 (60%) Option A (n = 4) 0 (0%) 4 (100%) 4 (100%) ART (n = 10) 4 (40%) 6 (60%) (mean age 8 years) with 69.6% demonstrating NNRTI mutations among presumed ART naive children. 21 The average age of infants at the time of first positive DBS was nearly 3 months (111 days) with a broad IQR (47-238 days). Tanzanian guidelines recommend initial DBS testing at 4-6 weeks of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Two studies from Dodoma, Tanzania, report resistance data from different populations including HIV-infected, ART naive pregnant women with 7.5% harboring NNRTI mutations 20 and ART naive children Maternal regimen sdNVP1tail (n = 10) 3 (30%) 7 (70%) 6 (60%) Option A (n = 4) 0 (0%) 4 (100%) 4 (100%) ART (n = 10) 4 (40%) 6 (60%) (mean age 8 years) with 69.6% demonstrating NNRTI mutations among presumed ART naive children. 21 The average age of infants at the time of first positive DBS was nearly 3 months (111 days) with a broad IQR (47-238 days). Tanzanian guidelines recommend initial DBS testing at 4-6 weeks of life.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Dodoma, Tanzania, reported a DBS amplification and sequencing rate of 44% compared with 95% from plasma samples in the same study. 21 Second, low levels of virus may have impacted sequencing success as samples with viral load <5,000 copies/ml (7%) were not able to be sequenced. The World Health Organization recommends programs relying on the use of DBS to maintain a higher threshold of 3,000-5,000 copies/ml of positivity until the sensitivity at lower thresholds has been confirmed.…”
Section: Discussionmentioning
confidence: 99%